Individual and Contextual Factors Associated With Maternal and Child Health Essential Health Services Indicators: A Multilevel Analysis of Universal Health Coverage in 58 Low- and Middle-Income Countries - Seun S. Anjorin; Abimbola A. Ayorinde; Oyinlola Oyebode; Olalekan A. Uthman (Kerman University of Medical Sciences, 2022)
Background  Universal health coverage (UHC) is part of the global health agenda to tackle the lack of access to essential health services (EHS). This study developed and tested models to examine the individual, neighbourhood and countrylevel determinants associated with access to coverage of EHS under the UHC agenda in low- and middle-income countries (LMICs). Methods  We used datasets from the Demographic and Health Surveys (DHSs) of 58 LMICs. Suboptimal and optimal access to EHS were computed using nine indicators. Descriptive and multilevel multinomial regression analyses were performed using R and STATA. Results  The prevalence of suboptimal and optimal access to EHS varies across the countries, the former ranging from 5.55% to 100%, and the latter ranging from 0% to 90.36% both in Honduras and Colombia, respectively. In the fully adjusted model, children of mothers with lower educational attainment (relative risk ratio [RRR] 2.11, 95% credible interval [CrI] 1.92 to 2.32) and those from poor households (RRR 1.79, 95% CrI 1.61 to 2.00) were more likely to have suboptimal access to EHS. Also, those with health insurance (RRR 0.72, 95% CrI 0.59 to 0.85) and access to media (RRR 0.59, 95% CrI 0.51 to 0.67) were at lesser risk of having suboptimal EHS. Similar trends, although in the opposite direction, were observed in the analysis involving optimal access. The intra-neighbourhood and intra-country correlation coefficients were estimated using the intercept component variance; 57.50%% and 27.70% of variances in suboptimal access to EHS are attributable to the neighbourhood and country-level factors. Conclusion  Neighbourhood-level poverty, illiteracy, and rurality modify access to EHS coverage in LMICs. Interventions aimed at achieving the 2030 UHC goals should consider integrating socioeconomic and living conditions of people.